Pharmacokinetics and safety of olaparib in patients with advanced solid tumours and mild or moderate hepatic impairment. Issue 9 (5th April 2020) - Rolfo, Christian; Isambert, Nicolas; Italiano, Antoine; Molife, L. Rhoda; Schellens, Jan H.M.; Blay, Jean‐Yves; Decaens, Thomas; Kristeleit, Rebecca; Rosmorduc, Olivier; Demlova, Regina; Lee, Myung‐Ah; Ravaud, Alain; et al.
Abstract : Aims: Olaparib, a potent oral poly(ADP‐ribose) polymerase inhibitor, is partially hepatically cleared. We investigated the pharmacokinetics (PK) and safety of olaparib in patients with mild or moderate hepatic impairment to provide dosing recommendations. Methods: This Phase I open‐label study assessed the PK, safety and tolerability of single doses of olaparib 300‐mg tablets in patients with advanced solid tumours. Patients had normal hepatic function (NHF), or mild (MiHI; Child–Pugh class A) or moderate (MoHI; Child–Pugh class B) hepatic impairment. Blood was collected for PK assessments for 96 hours. Patients could continue taking olaparib 300 mg twice daily for long‐term safety assessment. Results: Thirty‐one patients received ≥1 dose of olaparib and 30 were included in the PK assessment. Patients with MiHI had an area under the curve geometric least‐squares mean (GLSmean) ratio of 1.15 (90% confidence interval 0.72, 1.83) and a GLSmean maximum plasma concentration ratio of 1.13 (0.82, 1.56) vs those with NHF. In patients with MoHI, GLSmean ratio for area under the curve was 1.08 (0.66, 1.74) and for maximum plasma concentration was 0.87 (0.63, 1.22) vs those with NHF. For patients with mild or moderate hepatic impairment, no new safety signals were detected. Conclusion: Patients with MiHI or MoHI had no clinically significant changes in exposure to olaparib compared with patients with NHF. The safety profile of olaparib did not differ from a clinically relevant extent between cohorts. No olaparib tablet or capsule dose reductions are required for patients with MiHI or MoHI.